Perceptions of integrated crop-livestock systems for sustainable intensification in the Brazilian Amazon. (March 2019) - Cortner, O.; Garrett, R.D.; Valentim, J.F.; Ferreira, J.; Niles, M.T.; Reis, J.; Gil, J.
Highlights: Structural factors shape farmers' perceptions of integrated crop livestock systems. Adopters perceived large advantages from adopting ICLS, while most non-adopters did not. Supply chain and labor market limitations are perceived adoption barriers. Perceived unsupportive regulations and preferences for existing traditions also impede adoption. Improved credit, land tenure, infrastructure, and rural education may improve adoption. Abstract: Sustainable intensification of existing global croplands and rangelands is a pressing challenge to reconcile competing demands on land systems for food production and conservation of natural ecosystems. In Brazil, the world's second-largest beef-producing country, intensification of pasture-based production systems is central to both improving livelihoods and reducing deforestation, since low-productivity, low-income cattle ranches occupy a majority of the agricultural land area. Integrated crop-livestock systems (ICLS) present a promising opportunity in the array of possible agricultural intensification strategies for Brazil because they have the potential to reclaim vast areas of degraded pastures while mitigating greenhouse gas emissions. Much of the previous research on ICLS, particularly in Brazil, has focused on agronomic and economic aspects. Here we examine local perspectives of ICLS to better illuminate what other concerns, besides agronomic and economic outcomes, might guide farmers' decisions to adopt this (and other) agricultural intensification strategies. We are particularly interested in the degree to which structural factors interact with personal experiences to shape information and values and farmers' understanding of the costs and benefits of adopting a new technology. Using semi-structured interviews with a diverse sample of producers in four states in the Brazilian Amazon, we find that existing adopters perceived ICLS as a beneficial strategy for increasing the economic value and competitiveness of their farm, while most non-adopters did not. Ranchers in particular perceived intensification as a necessity to maintain their livelihood amidst declining profits and increased environmental oversight. However, both adopters and non-adopters described numerous structural barriers that impeded greater adoption of ICLS in the region, including problems obtaining qualified labor, a lack of marketing options, poor infrastructure, an unsupportive regulatory environment, and in some regions, poorly drained soils. Furthermore, non-monetary motives, such as maintaining one's existing quality of life and traditions, often drove decisions regardless of expected profit-maximization pathways. This work underscores the need to employ a more diverse set of policy tools beyond credit subsidies to encourage adoption of sustainable intensification strategies, including education programs, payments for the ecosystem services, and improved transportation and supply chain infrastructure that can support intensification and help create a climate of innovation.